Total ankle replacement conversion to Tibiotalocalcaneal Arthrodesis – Single lateral transfibular approach: Technical note - Raquel Lima Cunha, MD; Alexandre Castro, MD; António Madureira, MD; António Miranda, MD; Pedro Atilano Carvalho, MD; João Teixeira, MD (Foot & Ankle Surgery: Techniques, Reports & Cases)
The increasing popularity of total ankle replacements (TARs) has led to a corresponding rise in complications, necessitating effective salvage procedures for failed TARs. This article presents a innovative approach to converting a failed TAR to a tibiotalocalcaneal arthrodesis using a lateral, transfibular approach. This method offers an alternative approach to the traditional anterior approach, especially in patients with previous anterior wound complications. The procedure involves the use of a tricortical iliac graft to maintain limb height and promote bone fusion, with preservation of the lateral portion of fibula to enhance vascularization. Early results suggest that the lateral transfibular approach is a promising alternative for managing complex TAR failures, though long-term studies are needed to fully validate its efficacy. Level of Evidence: Level V - expert opinion.